Global decline in semen quality: ignoring the developing world introduces selection bias - deonandan, raywat; jaleel, marya (Université d'Ottawa | University of Ottawa, 2012)
Multiple studies from around the world have suggested that semen quality is declining globally. However, all studies suffer from variable semen sampling criteria, selection bias with respect to the types of men volunteering to participate, and a bias with respect to a tendency to examine only samples from high-income countries. This heterogeneity in approaches, especially given the undersampling of rural and less affluent men from low-income countries, calls into question researchers' claims of universally declining semen norms.
Keywords: human semen; quality; global; developing world